2022
DOI: 10.1097/gox.0000000000004013
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience Using a New Robotic Microsurgical System for Lymphatic Surgery

Abstract: Summary: Robotic microsurgery has emerged as a new technology with potential benefits for reconstructive surgery. We report the first-in-human use of the Symani surgical system to perform lympho-venous and arterial anastomosis for lymphatic reconstruction. In five patients, 10 robot-assisted anastomoses were performed. Next to lympho-venous anastomoses, two patients received a free vascularized lymph node transfer. Motion scaling was set to 10×. Visualization was either achieved with a 3D system or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 9 publications
2
47
0
15
Order By: Relevance
“…The feasibility and safety of using this device for microsurgery in humans have been previously demonstrated by our group. A further step is to assess the potential and the challenges of this innovative tool 2 . It is well known that microsurgery requires a specific set of skills, but despite the extensive training, there are factors intrinsic to the human hand, like tremor, precision, and accuracy, that are subjective and can be influenced by the psychological and physical status of the surgeon 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility and safety of using this device for microsurgery in humans have been previously demonstrated by our group. A further step is to assess the potential and the challenges of this innovative tool 2 . It is well known that microsurgery requires a specific set of skills, but despite the extensive training, there are factors intrinsic to the human hand, like tremor, precision, and accuracy, that are subjective and can be influenced by the psychological and physical status of the surgeon 6 .…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown the feasibility and safety in performing micro- and supermicrosurgical anastomosis in lymphatic reconstruction with the system. 2 The Symani Surgical System® was also used for a free flap in a post-traumatic upper limb reconstruction by Innocenti and his team 5 .…”
Section: Introductionmentioning
confidence: 99%
“…1 ) was designed to enhance reconstructive and microsurgery applications, and it received CE marking in 2019. 10 , 11…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, this system has been used in five clinical cases for the pharynx and lower leg reconstruction (personal communication with MMI, cases presented at Barcelona Breast Meeting 2020). Additionally, Lindenblatt et al confirmed the usage of the Symani System in the field of plastic and reconstructive surgery by presenting successful Symani-assisted lympho–venous anastomosis and lymph node transfer [ 30 ].…”
Section: Resultsmentioning
confidence: 99%